Gestión ambiental en el sistema de recojo de desechos sólidos urbanos del distrito de cascas, provincia de gran chimú, departamento de la libertad. Perú - 2010 - Torres Delgado, Froy (2010)
The collection of solid waste (MSW) is a problem that is increasing, due to inadequate environmental management that runs as in Cascas district, which results in poor service solid waste collection urban, they do not guarantee good health of the population and beautification. This paper proposes an Environmental Management Programme pickup system of urban waste at least, reduce urban pollution. For the effect was determined, the per capita (PPS) 0.765 Kg / h / day, 6 components, density, moisture Kg/m3.y 229.81 solid waste (77.76%) but also the number of turns of the unit collector (01 turn), modality and total collection (3296 Kg / day), service coverage percentage (121.36%.), number of units necessary gatherers (01 unit), the collection process, the routes, type of environmental management running Cascas Municipality and the level of knowledge and information on the environmental issue of the citizenry (68% unknown, on environmental issues). The work was aimed at mitigating the environmental impact by involving all the forces and improve the living conditions that contribute to improving the development, planning and implementation of measures for the biological balance of the biosphere, through a proposed treatment municipal solid waste Cascas, which in turn led to propose a Sustainable Environmental Management Plan.